A Retrospect on the Limits of Postcolonial Studies. Issue 1 (April 2015) - Parry, Benita
<x xml:space="preserve">Abstract</x> Benita Parry here examines the political horizons of postcolonial studies, arguing for the crucial role of Marxism in sustaining the revolutionary impetus of postcolonialist thought. Addressing the career of the late Edward W. Said, Parry points out that while Said's approach to criticism may initially have been philological, political purpose and direction were 'thrust upon him' through the situation of his native Palestine in the 1970s, together with the retreat from radicalism within academia. The Said of this period thus urged upon intellectuals the need to engage with injustice and oppression. Parry writes of Said's 'circuitous journey' that returned him, in his later works, to a critical approach that eschewed the political, and aimed to contain conflict through his notion of the 'contrapuntal.' While Said, with many postcolonial critics, did not subscribe to Marxism, Parry suggests that his work retained a thoughtful and complex respect for Marxists such as Lukács, Goldmann, Raymond Williams, and Adorno. For Parry, Said's repudiation of Marxism is 'of a different order' from that of other postcolonial critics who drag revolutionary figures such as Fanon and Gramsci into their own agenda by attempting to stabilise and attune their thought to the 'centre-left'. Parry goes on to criticise the editors of The Postcolonial Gramsci, for positing Marxist thinking as a restricting framework from which the editors aim to liberate Gramsci's writing. For Parry, these reappraisals of revolutionary thinkers constitute a new form of recuperative criticism that she terms 'the rights of misprision'. If this is a strategy for 'draining Marxist and indeed all left thought of its revolutionary impulses and energies', Parry insists, 'it is one to be resisted and countered, not in the interests of a sterile rigour, but – in Benjamin's words – to rescue the past and the dead, and a tradition and its receivers, from being overpowered by conformism'.